The real-life efficacy and safety of osimertinib in pretreated advanced non-small cell lung cancer patients with T790M mutation: a Turkish Oncology Group Study - YUMUK, PERRAN FULDEN; BAŞOĞLU TÜYLÜ, TUĞBA (SPRINGER, 2022)
Introduction Osimertinib, an irreversible third-generation EGFR-TKI, is the standard of care for second-line treatment of T790M-mutant advanced NSCLC patients whose disease progressed after first-line EGFR-TKI therapy. In this multicenter study, we aimed to determine the real-life efficacy and safety of Osimertinib in pretreated advanced NSCLC patients with T790M mutation. Materials and methods This retrospective trial included advanced T790M-mutant pretreated NSCLC patients who received Osimertinib from 24 different centers in Turkey. Primary endpoint was time-to-treatment discontinuation (TTD). Secondary endpoints were objective response rate (ORR), overall survival (OS), and safety. Results Of 163 patients, 68.7% had EGFR exon 19 deletion and 22.7% had exon 21 L858R mutation. Osimertinib was given as second-line treatment in 96 patients (58.9%) and third-line in 48 patients (29.4%). After median of 13-month follow-up, median TTD was 21.6 months with an 82.2% ORR. Estimated median OS was 32.1 months. Grade 3-4 adverse events were seen in 11.7% of the patients. Conclusion Osimertinib is a highly effective option in second- or third-line treatment of NSCLC patients with T790M mutation, with a favorable safety profile.
Keywords: Osimertinib; Non-small cell lung cancer; EGFR; T790M; Second line; CHEMOTHERAPY; THERAPY; PROGRAM; TIME